Apple fractions - Pallotta, Jerry; Bolster, Rob (New York : Scholastic, 2002)
Describes a variety of apples and uses them to introduce fractions.
"Cartwheel books."
Book Links (A.L.A.)
3.8
K-3
Keywords: Fractions -- Juvenile literature; Apples -- Juvenile literature; Fractions; Apples; Fractions; Apples